Global (Sustainable) Commercial Urbanism and Culture - Balsas, Carlos J.L. (Global Journal of Cultural Studies, 2023)
The decision makers of western cities have utilized commercial urbanism to help improve urban livability for several decades. The upgrade and redesign of shopping areas as well as the modernization of small and medium size retail establishments appear central to this goal. However, the unpredictability of technological innovations, lifestyles, consumer demand, and the uncertainty of global and regional markets contribute to the difficulty in delivering the most adequate and long-lasting urbanistic solutions. To what extent can professionals and elected officials utilize local cultures and regional identities to craft urban policies and programs capable of enabling flourishing businesses with both positive impacts in local economies and urban cultures? The purpose of this paper is to revisit a series of urban planning research programs, which the author studied over the past three decades in the Iberian Peninsula, the Americas, and Macau SAR. The research methods comprised literature reviews, public policy and case study analyses, teaching and research engagements, residence periods, and extended visits in Portugal, the northeast and southwest of the United States, Latin America, and Macau SAR. The argument is twofold: First, globalization is simultaneously homogenizing commercial landscapes while contributing to environmentally damaging car dependent lifestyles; and second, professionals ought to establish localized and culture-based (sustainable) commercial urbanism programs capable of assuring the long-term success of cities. The key finding is that livability assurance guarantees and cultural patterns are highly dependent on each city’s idiosyncratic characteristics such as size, place in the urban hierarchy, as well as historic roles performed in regional, national, and global dynamics.